Cardiac Hydatid Cyst: A Rare but Potentially Life-Threatening Presentation of Hydatid Disease - Kanhai Lalani; M. Sudhakar Rao; R. Padmakumar; Pankti Parikh; M. V. Ashwini; Ujwal teja Dhulipalla (Methodist DeBakey Cardiovascular Journal)
Cardiac echinococcosis is a rare and severe manifestation of hydatid disease. It is caused by parasitic infestation by the Echinococcus species and can lead to life-threatening complications. Diagnosis is difficult due to nonspecific symptoms, but echocardiography is a highly sensitive diagnostic method. Albendazole treatment is effective in managing these cysts and can be an alternative to surgery. A patient with multiple cardiac hydatid cysts was successfully treated with albendazole, highlighting the importance of prompt diagnosis and treatment to prevent life-threatening complications.